2016
DOI: 10.11604/pamj.2016.23.153.8208
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weight status on physical and mental health in Moroccan perimenopausal women

Abstract: IntroductionThere is a lack of information about fitness and other health indicators in women from countries such as Morocco. This study aims to explore the association of weight status with physical and mental health in Moroccan perimenopausal women.Methods151 women (45-65 years) from the North of Morocco were analyzed by standardized field-based fitness tests to assess cardiorespiratory fitness, muscular strength, flexibility, agility and balance. Quality of life was assessed by means of the Short-Form-36 He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Some studies have found significant relationships between levels of physical activity and serum lipid and lipoprotein levels [ 10 13 ], and body composition [ 14 16 ]. However, these associations are not completely consistent in the literature [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found significant relationships between levels of physical activity and serum lipid and lipoprotein levels [ 10 13 ], and body composition [ 14 16 ]. However, these associations are not completely consistent in the literature [ 17 ].…”
Section: Introductionmentioning
confidence: 99%